(untitled) (Journal of Medicine, 2016)
Tuberous Sclerosis Complex (TSC) is a neurocutaneous syndrome manifested by involvement of multiple system including CNS, kidney, skin, heart, lungs & eye. It is usually characterized by triad of skin lesions (96%), seizures (90%) & mental retardation (70%). Most common lesions associated with TSC are angiofibroma of face, ashleaf macules, shagreen patches, subependymal nodules, cortical tubers, mental retardation &angiomyolipoma of kidney. Here we report a case of a 14 years old girl who presented with recurrent episodes of convulsion, mental retardation & progressive weakness of right side of body. We investigated the patient to find out the etiology of her illness. After cranial imaging & other necessary investigations several major & minor criteria were established, which helped us to reach the final diagnosis J MEDICINE July 2016; 17 (2) : 125-129